UTHM Lost and Found Management System - Shahzan, Nurul Fatihah; Arbaiy, Nureize (Applied Information Technology And Computer Science, 2025)
Currently, there is a unit at the Universiti Tun Hussein Onn Malaysia (UTHM) that manages lost and found items information through an unofficial digital platform as the foundation for its lost and found goods management system. The Telegram and WhatsApp apps are utilized to share information about the item's location and description. This method is thought to be less efficient and safe. Because the project recognizes the shortcomings of the present informal approach, a web-based system is being developed to enhance the handling of lost and found items at UTHM. Since they are in charge of reporting and keeping an eye on missing objects and UTHM, the students and the community at large are the primary users. The Lost & Found Centre serves as the administratoristrative representative for system operations and facilitates effective item-handling processes on campus. A centralized system that streamlines the matching and reporting processes will result from the prototype that was developed. Administratoristrative tools for effective management are available, along with a simple interface for reporting and monitoring lost items. The lost and found procedure on campus is made better with the prototype's improved procedures, database, and communication.